PENGARUH VAKSIN COVID-19 MULTIEPITOP DENGAN KITOSAN TERHADAP HISTOPATOLOGI JANTUNG MENCIT BALB/C - Sayu Putu Yuni Paryati; Endah Hamidah Abbas; Wahyu Rizky Wibowo (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2026)
The multi-epitope COVID-19 vaccine contains epitopes designed to induce an immune response, using SARS-CoV-2 as the model antigen. This study examined its effects on the cardiac histopathology of male BALB/c mice. A total of 25 mice were divided into five groups: a negative control that received no treatment (K), a 500 µg multi-epitope COVID-19 vaccine evaluated on day 7 after the second dose (P1), a 500 µg multi-epitope COVID-19 vaccine evaluated on day 14 after the second dose (P2), a 500 µg multi-epitope COVID-19 vaccine formulated with chitosan and evaluated on day 7 after the second dose (P3), and a 500 µg multi-epitope COVID-19 vaccine formulated with chitosan and evaluated on day 14 after the second dose (P4). Myocardial tissue was examined microscopically for inflammatory cell infiltration, degeneration, and necrosis. The study used a completely randomized design with a post-test-only control group. Based on the Dallas criteria, no myocarditis was identified, with or without necrosis, as all groups showed no inflammatory cell infiltration. However, vacuolar and fatty degeneration were observed in both the negative control and the treatment groups (P1, P2, P3, P4), which were likely unrelated to the administration of the multi-epitope COVID-19 vaccine, with or without chitosan adjuvant. These findings indicate that the vaccine induces an immune response without causing hyperactivation or hypersensitivity, so the response remains limited and controlled. Keywords: cardiac histopathology, cardiomyocyte degeneration, chitosan adjuvant, COVID-19, multi-epitope vaccine DOI : 10.35990/mk.v9n1.p23-34